Investigating the Potential Effect of Commiphora myrrha on the Pharmacokinetics of Theophylline, a Narrow Therapeutic Index Drug - Al-Jenoobi, F. I.; Ahad, A.; Raish, M.; Al-Mohizea, A. M.; Alam, M. A. (Drug Research, 2015)
Aim: The present study was conducted to investigate the effect of commonly used herb Commiphora myrrha on the pharmacokinetic profile of theophylline (narrow therapeutic index drug) in rabbits.Methods: In the experimental groups, theophylline (16 mg/kg) was given orally to the rabbits. Where aqueous saline suspension of Commiphora myrrha (176 mg/kg, p.o.), was given to the rabbits and the blood samples were withdrawn at different time intervals (0, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 12, 24 and 36 h) from marginal ear vein after dosing and theophylline in plasma was analyzed by HPLC method.Results: It was observed that there a significant differences in the Cmax, AUC, AUMC, t1/2, and MRT of theophylline when coadministered with Commiphora myrrha which indicate that the herb affect the metabolism and elimination when coadministered with theophylline.Conclusion: Our results suggested that concurrent use of investigated herb alters the pharmacokinetics of theophylline. Confirmation of these results in human studies will warrant changes in theophylline dose or frequency when coadministered with herb under consideration.
Keywords: bioavailability; cytochrome P4501A; disposition; herb-drug interaction